Design studies towards a 4 MW 170 GHz coaxial-cavity gyrotron - Beringer, Matthias Hermann (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2011)
In this work the feasibility of a 4 MW 170 GHz coaxial-cavity gyrotron for continuous wave operation is demonstrated. For the first time complete physical designs of the major gyrotron components are elaborated. In a first step, one possible new operating mode is determined, followed by the development of detailed physical designs of the major gyrotron components: Diode and triode type electron gun, coaxial cavity, two-beam quasi-optical output coupler and depressed collector.